2015
DOI: 10.1002/stem.2076
|View full text |Cite
|
Sign up to set email alerts
|

Brief Report: Human Mesenchymal Stem-Like Cells Facilitate Floating Tumorigenic Cell Growth via Glutamine-Ammonium Cycle

Abstract: How mesenchymal stem cells (MSCs) promote tumor growth remains incompletely understood. Here, we show that mesenchymal stem-like cells (MSLCs) are commonly present in malignant pleural effusion or ascites of cancer patients, where they directly interact with tumor cells. Chemokines and chemokine receptors, especially the CCL2/CCR2 pathway, are involved in this interaction. SIGNIFICANCE STATEMENTPatients with solid primary tumors may develop malignant pleural effusion or ascites, posing a formidable challenge … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 26 publications
(32 reference statements)
0
5
0
Order By: Relevance
“…Notably, the migration to tumor of MDSCs depended mainly on CCL2/CCR2 pathway [ 38 ]. More recently study revealed that, mesenchymal stem-like cells(MSLCs), the progenitor cells of fibroblast and adipocyte, which could migrate to tumor sites and then promote tumor growth, were also recruited by CCL2/CCR2 pathway [ 39 ]. Another article clarified that CCR2 participates in the recruitment of bone marrow-derived fibroblasts into the kidney during the development of renal fibrosis, thus we speculated CCR2 may promote tumor development by recruiting some bone marrow-derived fibroblasts into the tumor sites and then become cancer associated fibroblasts(CAF) in the tumor microenvironment [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Notably, the migration to tumor of MDSCs depended mainly on CCL2/CCR2 pathway [ 38 ]. More recently study revealed that, mesenchymal stem-like cells(MSLCs), the progenitor cells of fibroblast and adipocyte, which could migrate to tumor sites and then promote tumor growth, were also recruited by CCL2/CCR2 pathway [ 39 ]. Another article clarified that CCR2 participates in the recruitment of bone marrow-derived fibroblasts into the kidney during the development of renal fibrosis, thus we speculated CCR2 may promote tumor development by recruiting some bone marrow-derived fibroblasts into the tumor sites and then become cancer associated fibroblasts(CAF) in the tumor microenvironment [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have highlighted the critical role of TRCs in regulating the effect of immune cells on tumors. 8 On the one hand, TRCs themselves effectively evade immune-derived killing by (1) producing immunosuppressive molecules; 9 (2) recruiting immunosuppressive cells; 10 (3) losing antigen processing and presentation machinery and downregulating the expression of MHC I and co-stimulatory molecules. 11 On the other hand, tumorigenic TRCs profoundly reset immune cells, including macrophages and regulatory T cells into tumor-promoting ones.…”
Section: Introductionmentioning
confidence: 99%
“…Several recent published studies investigated ADSCs-MCF-7 communication in vitro. For example, Tang et al (2015) showed that mesenchymal stem cells (MSCs) are recruited to malignant fluids by a tumorcell-derived chemokine-mediated signaling pathway on the MSC. TGF-β can alter tight junction formation in the mammary epithelium and induce a number of embryonic signaling pathways, including the Wnt, Notch, and Hh pathways.…”
Section: Discussionmentioning
confidence: 99%